Analysis of Dairy Farm Management Strategy Development in North Sulawesi - Jolyanis Lainawa; Jemmy E.O. Rawis; Very L.H Rembang (International Journal of Applied Business and International Management, 2020)
This research is intended to find a strategy model for developing a dairy farm in North Sulawesi. This is considered important since it will only be developed by the local government in response to the increasing demand for milk and beef, while the availability of production decreases. The results of the analysis state that the long-term management strategy for developing a dairy farm in North Sulawesi is largely determined by building the driving forces of production and markets.